1979
DOI: 10.1002/1097-0142(197910)44:4<1215::aid-cncr2820440408>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

5 FU infusion with mitomycin-C vs. 5 FU infusion with methyl-CCNU in the treatment of advanced upper gastrointestinal cancer. A Southwest oncology group study

Abstract: A randomized trial was conducted by the Southwest Oncology Group (SWOG) in advanced carcinoma of the stomach and pancreas. Patients were assigned to receive monthly 5-fluorouracil 96-hour continuous infusions with either bolus mitomycin-C or oral methyl-CCNU. Mitomycin-C and methyl-CCNU were administered every eight weeks. The 5 FU-mitomycin combination produced a 14% and 22% response rate in disseminated stomach and pancreatic carcinoma, respectively. The combination of infusion 5 FU and methyl-CCNU achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

1980
1980
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 7 publications
0
18
0
2
Order By: Relevance
“…Responses to MMC as a second line agent after 5-FU are likely to be low. This is suggested by several randomized comparisons of 5-FU to 5-FU plus MMC for treating colorectal cancer which failed to show additive effects (Buroker et al, 1978;Richards et al, 1986), although a small additive effect on response rather than survival was reported (Ross et al, 1997). However, only one response was observed in 72 patients treated with MMC after 5-FU in phase II trials (Hartmann et al, 1998;Migeod et al, 1988;Zaniboni et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…Responses to MMC as a second line agent after 5-FU are likely to be low. This is suggested by several randomized comparisons of 5-FU to 5-FU plus MMC for treating colorectal cancer which failed to show additive effects (Buroker et al, 1978;Richards et al, 1986), although a small additive effect on response rather than survival was reported (Ross et al, 1997). However, only one response was observed in 72 patients treated with MMC after 5-FU in phase II trials (Hartmann et al, 1998;Migeod et al, 1988;Zaniboni et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…Natomiast połączenie 5-FU z cisplatyną [77][78][79] oraz 5-FU z cisplatyną i interferonem [80] nie zwiększa przeżycia w porównaniu z samym 5-FU. Podobnie, terapie łączone obejmujące 5-FU i ifosfamid [81], 5-FU i CCNU [82] oraz 5-FU i mitomycynę C [83,84] nie zwiększają przeżycia w porównaniu z 5-FU w monoterapii. Siedem badań o stosunkowo dobrej jakości [85][86][87][88][89][90][91] dowodzi, że terapia FAM (5-FU, doksorubicyna, mitomycyna C) nie przynosi korzyści w zaawansowanym raku trzustki, a wręcz wiąże się ze zwiększoną toksycznością.…”
Section: Terapia łąCzona Z Zastosowaniem 5-fluorouracylu W Zaawansowaunclassified
“…These compounds were also associated with frequent hematologic and renal toxicities [3][4][5][6][7] and consequently were not incorporated into standard chemotherapy regimens. With such limited therapeutic options, treatment for colorectal cancer tended to be nihilistic, few advances were made, and the outlook for patients with colorectal cancer was poor.…”
Section: Evolution Of Fluoropyrimidine Therapymentioning
confidence: 99%